2010
DOI: 10.1016/j.ejso.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of cetuximab, capecitabine and radiotherapy in neoadjuvant treatment of patients with locally advanced resectable rectal cancer

Abstract: Please cite this article as: Velenik V, Ocvirk J, Oblak I, Anderluh F. A phase II study of cetuximab, capecitabine and radiotherapy in neoadjuvant treatment of patients with locally advanced resectable rectal cancer, European Journal of Surgical Oncology (2009Oncology ( ), doi: 10.1016Oncology ( /j.ejso.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 27 publications
0
24
1
1
Order By: Relevance
“…Additional chemotherapeutic agents that have been studied in this context include oxaliplatin 13,14 and cetuximab. 15,16 These resulted in a pCR rate of 8e19%, which is lower than the 24.4% observed in our study. Although adding irinotecan 17 resulted in a higher pCR rate of 26%, the incidence of acute Grade 3e4 toxicity was as high as 42%, and hence, this therapy cannot be well tolerated by most patients.…”
Section: Discussioncontrasting
confidence: 82%
“…Additional chemotherapeutic agents that have been studied in this context include oxaliplatin 13,14 and cetuximab. 15,16 These resulted in a pCR rate of 8e19%, which is lower than the 24.4% observed in our study. Although adding irinotecan 17 resulted in a higher pCR rate of 26%, the incidence of acute Grade 3e4 toxicity was as high as 42%, and hence, this therapy cannot be well tolerated by most patients.…”
Section: Discussioncontrasting
confidence: 82%
“…Details of the eligibility criteria, pretreatment evaluation, RT, chemotherapy, cetuximab administration, and surgery have already been published and are briefly specified later (9,10,12,13).…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Comparable results were presented by other trials [17,18,19]. Machiels et al [17] reported the clinical results of a phase I/II study combining cetuximab and standard CRT - 1.8 Gy, 5 days/week for 5 weeks, total dose 45 Gy, 3D conformal technique and capecitabine 650-825 mg/m 2 orally twice daily for the duration of RT - in the preoperative treatment of 40 patients with LARC.…”
Section: Egfr Inhibitionmentioning
confidence: 53%
“…In total, 37 patients underwent surgery and pCR was recorded in 5% ( n = 2) of cases. Velenik et al [18] assessed neoadjuvant cetuximab with fluoropyrimidine-based CRT (capecitabine 825 mg/m 2 twice daily with RT of 45 Gy) in 37 LARC patients. Two patients presented with grade 3 acneiform rash and 2 patients with grade 3 diarrhea.…”
Section: Egfr Inhibitionmentioning
confidence: 99%